Karakteristik Remaja Pelaku dan Korban Bullying Meminta Uang Dengan Paksa (Memalak) - Ani Wardah; Nurul Auliah; Nurmiati (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2020)
This study aims to describe the characteristics of young perpetrators and victims of bullying asking for money by force (insulting). This research uses a qualitative approach with a qualitative descriptive design. Subjects were 4 (four) adolescents, namely one perpetrator and three victims of bullying forcibly asking for money (insulting) with an age range of 13-17 years. Data collection techniques used were observation, interviews, and documentation. The data analysis techniques used were data reduction, data presentation, and drawing conclusions and verification. The results showed that the characteristics of young perpetrators and victims of bullying asking for money by force (insulting) are factors that influence young people who do bullying are family, economy, personality, popularity. The factors that influence the behavior of the victims of bullying are personality, namely they do not have the power to resist, are helpless because they are threatened, and do not want something worse to happen. The self-concept of adolescents bullying is showing negativity, that is, they perceive themselves as having power. Meanwhile, the self-concept of youth victims of bullying is negative, that is, they perceive themselves as weak, powerless to refuse the perpetrator's request. The ability to manage emotions among bullies is in the category of not being able to manage emotions, while youth victims of bullying are in the category of being able to manage emotions well. The self-disclosure of teenagers bullying tends to be closed, and youth victims of bullying tend to be closed off.